If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(6n-8)=-36-8n
We simplify the equation to the form, which is simple to understand
-3(6n-8)=-36-8n
Reorder the terms in parentheses
+(-18n+24)=-36-8n
Remove unnecessary parentheses
-18n+24=-36-8n
We move all terms containing n to the left and all other terms to the right.
-18n+8n=-36-24
We simplify left and right side of the equation.
-10n=-60
We divide both sides of the equation by -10 to get n.
n=6
| 3(x-5)=2x-15 | | 5(15n+5)=8n-9 | | 7y-8=11y+16 | | x-9=-5+4 | | 6x^2+4x=2 | | 4(6x+8)=7-x | | 8b-4=1+7b | | 4x^2+49x+16=0 | | -8-4=4x+8-3x | | 2x=5+5 | | -8-4=4x+8-3 | | 8v-1-2+15=4v-3+v | | 8v-1-2+15=4v-3+ | | -120-10x=10x+20x | | -50+0.5x=153.5 | | 4a-(9-3a)=9a-1 | | -120-10x=10x+10x | | 8(3x-6)=-240 | | y^2-2y-3x-14=0 | | 99+6u=3u | | 5y=6x+20 | | 108=16x^2-22x+220 | | 2x=12-y | | 2x^2-5x-25= | | -5(1+7n)=-180 | | 11(x-8)=-2-9 | | X+0.5x+x+5=100 | | 3(4x-9)=28 | | -16=4-2m-8m | | x(2-x)=3(x-4) | | 114-3x=24x+16 | | -6-6(y+2)=2y-(4y-10) |